Contagion Analysis of Plantation Commodity Producing Regions in Aceh Province Using Bayesian Inference - Juliawati; Mukti Qamal; Said Fadlan Anshari (Faculty of Engineering, Malikussaleh University, 2024)
The commodity-producing region is one of the plantation sectors with significant potential for economic growth in Aceh Province. The spread level between commodities owned by regions within the network is called “contagion,” which means that one commodity will influence a region, leading to a greater focus on that commodity within the network, and a region will influence other regions. With the diversity of commodities across various areas, a comprehensive analysis and visualization of the network formed among commodity producing regions are conducted using a Social Network Analysis (SNA) approach. Thus, Bayesian inference can reveal the network of each region that has relationships among the variables used to form a graph with the desired representation. This network analysis result can provide an overview of Aceh Province's plantation data through the network graph visualization among commodity-producing regions and the network graph of commodity production levels by region. Keywords: Aceh; Contagion Analysis; Social Network Analysis